Trends, prospects, and challenges in Asian E-governance - Sodhi, Inderjeet Singh (Advances in electronic government, digital divide, and regional development (AEGDDRD) book series, 2016)
"This book addresses some of the ongoing struggles of fast-developing nations such as China, India, and Indonesia within the context of electronic government, illustrating how digital tools can assist developing nations in maintaining their prospects for future growth and expansion"--